Durability effect of nano-SiO2/Al2O3 on cement mortar subjected to sulfate attack under different environments. (1st April 2023) - Zhang, Ai; Ge, Yong; Du, Sen; Wang, Guangzhi; Chen, Xin; Liu, Xu; Li, Hebin
Abstract: Ambient humidity and air pressure have significant effects on the durability of cement-based materials subjected to sulfate attack. This paper investigated the durability performance of cement paste and cement mortar containing nano-SiO2 (NS) and nano-Al2 O3 (NA) attacked by Na2 SO4 solution under low air pressure (60 kPa, LP) and normal air pressure (101 kPa, NP) environments. The results showed that supersaturated Na2 SO4 solution could crystallize in the pores of mortar and deposit on the surface of mortar, accompaning by the transformation from Na2 SO4 ∙10H2 O with fibrous to Na2 SO4 with powder. The presence of low air pressure environment exacerbated the capillary transport rate and the water evaporation rate, resulting in a severer salt efflorescence. However, the incorporation of NS/NA could reduce the adsorption height of the salt solution on the surface of the mortar and thus alleviate the Na2 SO4 -induced damage. Moreover, the flexural/compressive strength of nano-modified mortar subjected to Na2 SO4 attack under NP and LP environments were enhanced due to the nucleation effect and chemical activity of NS and NA. Furthermore, the addition of nanomaterials decreased the porosity and the amount of harmful pores above 50 nm in the samples and increased the consumption the erodible Ca(OH)2, reducing the generation of Na2 SO4 -induced corrosion products. Among them, the system containing NA at 0.5 wt% performed better, which is of great significance for the protection of concrete components exposed to sulfate attack in the practical engineering. Highlights: Low air pressure accelerates the corrosion rate of cement mortar partially immersed in the Na2 SO4 solution. The incorporation of 0.5 wt % NA performs better to mitigate Na2 SO4 attack. The nano-modification decreases the porosity and the number of harmful pores above 50 nm. The modification of nano-SiO2 /Al2 O3 is based on the nucleation, reactivity, filling and homogeneity effects.